Methodical approaches to recreational and tourist cycles - fundamentals of recreational and tourist nature management. - Zayachyk, Myroslav; Кілінська, Клавдія; Яворська, Вікторія; Сухий, Петро Олексійович (My University, 2021)
The article analyzes the essence and significance of recreational and tourist activities as a component of recreational and tourist cycles. Thus, recreation and tourism can be considered as a separate large block of nature -recreational and tourist nature management (RTP), which allows not only each person to use a favorable resource base for recreation, but also leads to changes in this area and the formation, as a result, multilevel ecological situations. The authors argue that a scientifically sound system of recreational and tourist resources is being formed, which helps tourists and vacationers to be aware of the geographical locationof certain objects of recreation and contemplation.
Методичні підходи до рекреаційно-туристичного циклу - основи рекреаційн -туристичного природокористування
Keywords: recreation; tourism; rest; nature management; region